ENGLISH PHRASAL COMPOUNDS AND THEIR INDONESIAN TRANSLATION IN SPIDER-MAN: INTO THE SPIDER-VERSE MOVIE - Yohanes A Deo Damar Krisnadi; Priyatno Ardi (ELTR Journal, 2018)
This research analyzed the types of English phrasal compounds and the degree of acceptability of the Indonesian translation of the English phrasal compounds in Spider-Man: Into the Spider-Verse movie. This research aims to know the types of English phrasal compounds found in the Spider-Man: Into the Spider-Verse movie and the acceptability of the translation of the English phrasal compounds in the Indonesian subtitle. The research was qualitative research and the research used document analysis. In gathering the data, two tables were used to collect the data. The first table was about the types of English phrasal compounds according to Hockett (1958) and the second table was the translation acceptability of English phrasal compounds according to Larson (1984). The researchers found 102 English phrasal compounds. The researcher discovered that phrasal verbs became the most frequent phrasal compounds. There were 97 phrasal verbs (95.1%). The researcher found 5 compound nouns (4.9%). Meanwhile, there was no compound adjective in the movie. Furthermore, the translation of English phrasal compounds into Indonesian was acceptable. All of the one hundred and two (102) translation fulfilled the three criteria of a good translation